A pharmacological network for lifespan extension in Caenorhabditis elegans - Ye, Xiaolan (BlackWell Publishing Ltd, 2014)
One goal of aging research is to find drugs that delay the onset of age-associated disease. Studies in invertebrates, particularly Caenorhabditis elegans, have uncovered numerous genes involved in aging, many conserved in mammals. However, which of these encode proteins suitable for drug targeting is unknown. To investigate this question, we screened a library of compounds with known mammalian pharmacology for compounds that increase C. elegans lifespan. We identified 60 compounds that increase longevity in C. elegans, 33 of which also increased resistance to oxidative stress. Many of these compounds are drugs approved for human use. Enhanced resistance to oxidative stress was associated primarily with compounds that target receptors for biogenic amines, such as dopamine or serotonin. A pharmacological network constructed with these data reveal that lifespan extension and increased stress resistance cluster together in a few pharmacological classes, most involved in intercellular signaling. These studies identify compounds that can now be explored for beneficial effects on aging in mammals, as well as tools that can be used to further investigate the mechanisms underlying aging in C. elegans.